Transformasi Kebijakan Kurikulum Pendidikan di Indonesia Sebagai Landasan Pengelolaan Pendidikan - Aziz, Farhan Zabdul; Setiawan, Farid; Hariadi, David; Setianingsih, Faradina Nur (Attractive : Innovative Education Journal, 2022)
The purpose of this study was to determine the changes in curriculum policy that occurred in Indonesia. The method used in this study is library research which in conducting this research is to obtain or collect compiler information using the help of internet applications to browse books, journals and other scientific works related to the research topic. Then the data is summarized and focused on the main things and then arranged with predetermined themes and patterns. The results of the discussion in this study are that Indonesia has undergone various changes in its educational curriculum, from the beginning of independence to the present, which includes curriculum policies from 1947 to 2013. In the end, future education requires policy designs to respond to the hopes and challenges of the times. The transformation is formed because of the level of the learning process in learning activities by students, so that here students have good goals according to expectations, and also become potential leaders through the world of education as the nation's hope. Keywords: Education Curriculum Policy, Curriculum Policy, Curriculum Policy Transformation